Acousmatic Storytelling. Issue 3 (11th November 2016) - Amelides, Panos
Abstract : The purpose of this article is to explore the idea of relating storytelling with acousmatic music in the creation of a hybrid vehicle for transmitting stories. The concept of acousmatic storytelling is introduced, illustrated by the example of one of my own works which was created with the elements and techniques of storytelling as its conceptual basis. The article continues to investigate concepts of acousmatic storytelling in works from the repertoire of electroacoustic music, with composers such as Ferrari, Westerkamp, Derbyshire, Cousins and Young providing especially pertinent examples. Acousmatic storytelling integrates interviews, archival recordings, soundscape recordings, sonic icons and music quotations; the microphone becomes a time machine, 'thought capturer' and a conduit for conveying cultural information, elements which, combined with the sonic world composed in the studio, create a hybrid form. The concepts introduced in this article are useful for all those working with recorded sound, offering an approach to sonic creativity based on storytelling techniques and the way we experience past events through memory and sound recording. Acousmatic storytelling transmits a unique version of a story to the mind of the listener, who participates in the creation of the story and acts as co-creator of that story as experienced. In applying the methodology of interviews as well as researching past events and 'writing' about them, acousmatic storytelling composers can also be seen as historians and journalists.